The head of the Jews in Egypt In the Fātimid epoch And consideration of the Complaints and Petitions of the Jews by Genizah Documents - Abd-Alhadi Moussa, Mohammad Joma; Mahmoud Al-Qousi, Atiya Ahmed (The Algerian Historical Journal, 2026)
The purpose of this study is to deal with the head of the Jewish community in Egypt in the Fatimid epoch and his consideration of the complaints and petitions of the Jews from the reality of the Genizah documents; In addition to dealing with the emergence of this position (the Najid), its powers, and its important role in the Jewish community in Egypt during the Fatimid epoch; Through the documents contained in the Cairo Geniza. Under the Fatimid, the office of the Chief of the Jews served as the chief legal and religious representative of the entire Jewish community in government, responsible for pleading the interests of each particular section of society. The study is based on the historical, descriptive and analytical method.